2017
DOI: 10.1080/02640414.2017.1298826
|View full text |Cite
|
Sign up to set email alerts
|

Technique analysis in elite athletes using principal component analysis

Abstract: The aim of this study was to advance current movement analysis methodology to enable a technique analysis in sports facilitating (1) concurrent comparison of the techniques between several athletes; (2) identification of potentially beneficial technique modifications and (3) a visual representation of the findings for feedback to the athletes. Six elite cross-country skiers, three world cup winners and three national elite, roller ski skated using the V2 technique on a treadmill while their movement patterns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
1
58
0
3
Order By: Relevance
“…All of the following PCA-based calculations were computed using a software package called "PManalyzer" [39], which is provided through open access. As a first analysis step, gaps in the marker trajectories were filled [40,41], then the data from each trial was normalized by subtracting the mean posture and dividing by the trial's mean Euclidean distance [29,32], finally, the marker coordinates were weighed according to the relative body mass, which they represent [29,42]. This normalization was designed to remove anthropometric differences while preserving the relative amplitude of the marker movements and to ensure that each participant equally affected the PCA output [29,32].…”
Section: Processing Of Kinematic Data: Calculation Of Principal Movemmentioning
confidence: 99%
“…All of the following PCA-based calculations were computed using a software package called "PManalyzer" [39], which is provided through open access. As a first analysis step, gaps in the marker trajectories were filled [40,41], then the data from each trial was normalized by subtracting the mean posture and dividing by the trial's mean Euclidean distance [29,32], finally, the marker coordinates were weighed according to the relative body mass, which they represent [29,42]. This normalization was designed to remove anthropometric differences while preserving the relative amplitude of the marker movements and to ensure that each participant equally affected the PCA output [29,32].…”
Section: Processing Of Kinematic Data: Calculation Of Principal Movemmentioning
confidence: 99%
“…These identified variables 143 are represented in a compact feature variable (Mannini & Sabatini, 2010). (Gløersen, Myklebust, Hallén, & Federolf, 2018;Young & 145 Reinkensmeyer, 2014), vector coding techniques (Hafer & Boyer, 2017) and empirical cumulative 146 distribution functions (ECDF) (Plötz, Hammerla, & Olivier, 2011). An ECDF approach has been 147 shown to be advantageous over PCA as it derives representations of raw input independent of the and analysis of IMU data for sports application and vision-based human activity recognition, see and (Bux et al, 2017), respectively.…”
mentioning
confidence: 99%
“…(Tenforde, Borgstrom, Outerleys, & Davis, 2019)) and previous running experience. Indeed, several studies have shown technique to differ between (Brisson & Alain, 1996;Glazier & Lamb, 2017;Gloersen, Myklebust, Hallen, & Federolf, 2018;Morriss, Bartlett, & Fowler, 1997) and within individuals (Glazier & Lamb, 2017;Horst, Eekhoff, Newell, & Schollhorn, 2017;Riza, 2017). It can therefore be questioned to what extent an "ideal" technique should be aspired, for example, by using deviations from the average movement by 1 standard deviation as a criterion for technique modification (Bowser et al, 2018).…”
Section: When To Modify Running Technique?mentioning
confidence: 99%